Variability in body weight precedes diagnosis in dementia: A nationwide cohort study. Issue 11 (28th August 2020) - Ha, Jane; Kwon, Yeongkeun; Kwon, Ye‐Ji; Kim, DaHye; Han, Kyungdo; Jang, Mi; Park, Sungsoo; Nam, Ga Eun; Kim, Yang Hyun; Kim, Do Hoon; Park, Yong Gyu; Cho, Kyung‐Hwan
Abstract: Background: While there have been disagreements concerning whether obesity and increase in body weight elevate the risk of dementia, variability in body weight has been recently recognized as a new biometric associated with a high risk for a number of diseases. This nationwide, population‐based cohort study examined the association between body weight variability and dementia. Methods: A total of 2, 812, 245 adults (mean age, 51.7 years; standard deviation, 8.6) without a history of dementia who underwent at least three health examinations between 2005 and 2012 in a nationwide cohort were followed‐up until the date of dementia diagnosis (based on prescribed drugs and disease code) or until 2016 (median follow‐up duration, 5.38 years; interquartile range, 5.16–5.61). Cox regression models were used to evaluate the risk of Alzheimer's disease and vascular dementia according to body weight variability. Results: The hazard ratios (95% confidence intervals) of the highest quartiles of variability were 1.42 (1.35–1.49) for Alzheimer's disease and 1.47 (1.32–1.63) for vascular dementia compared to the lowest quartile group as a reference. This association was consistent in various subgroup analyses and sensitivity analyses. Conclusions: Body weight variability could predict Alzheimer's disease and vascular dementia, which may provide new insights into the prevention and management of dementia. Abstract : Body weight variability could be a potential risk factor for Alzheimer's disease and vascular dementia, which may provide new insights for dementia prevention.